2018
DOI: 10.1007/s12325-018-0753-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of Budesonide/Formoterol Fumarate Easyhaler® for Patients with Poorly Controlled Obstructive Airway Disease: a Real-World Study of Patient-Reported Outcomes

Abstract: IntroductionThe effectiveness of inhaled therapies can be influenced by many factors, including the type of inhaler, which may have clinical implications. We report a real-world, multicenter, open-label, non-randomized, non-interventional study conducted by 200 pulmonologists across 200 centers in Hungary. The effectiveness of budesonide/formoterol inhalation therapy in daily clinical practice, delivered via the Bufomix Easyhaler®, was evaluated in patients with asthma, chronic obstructive pulmonary disease (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…This was a post hoc subanalysis of a 12-week, real-world, multicenter, open-label, non-randomized, non-interventional, single-arm study, conducted across 200 Hungarian centers between May 1, 2016 and December 31, 2017 (National Pharmaceutical Institute of Pharmacy and Nutrition of Hungary; trial registration number: OGYÉ I/13942-5/2016) [24]. The study consisted of three visits and assessed treatment effectiveness in patients diagnosed with asthma or COPD who switched from their current inhaler to B/F Easyhaler.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This was a post hoc subanalysis of a 12-week, real-world, multicenter, open-label, non-randomized, non-interventional, single-arm study, conducted across 200 Hungarian centers between May 1, 2016 and December 31, 2017 (National Pharmaceutical Institute of Pharmacy and Nutrition of Hungary; trial registration number: OGYÉ I/13942-5/2016) [24]. The study consisted of three visits and assessed treatment effectiveness in patients diagnosed with asthma or COPD who switched from their current inhaler to B/F Easyhaler.…”
Section: Methodsmentioning
confidence: 99%
“…Budesonide/formoterol fumarate (B/F) Easyhaler Ò (Orion Pharma, Espoo, Finland) is a multidose dry powder inhaler containing a combination of the inhaled corticosteroid, budesonide, and the long-acting b2-adrenergic agonist, formoterol fumarate, indicated for the treatment of adults with COPD and/or asthma, and adolescents aged 12-17 years with asthma [22], and approved in several European countries. Two non-randomized, open-label, singlearm studies conducted in Poland and Hungary have confirmed the effectiveness of the B/F Easyhaler for the treatment of asthma [23], COPD, and asthma-COPD overlap (ACO) [24] in everyday clinical practice. In the latter study, 30.4% of patients were inhaler-naïve and 69.6% switched to the B/F Easyhaler from other inhalers; after 12 weeks of treatment, significant improvements in lung function, disease control, and HRQoL (all p B 0.002) were observed in both inhaler-naive patients and switchers [24].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations